C9orf72 ALS/FTD dipeptide repeat protein levels are reduced by small molecules that inhibit PKA or enhance protein degradation. (18th November 2021) - Licata, Nausicaa V; Cristofani, Riccardo; Salomonsson, Sally; Wilson, Katherine M; Kempthorne, Liam; Vaizoglu, Deniz; D'Agostino, Vito G; Pollini, Daniele; Loffredo, Rosa; Pancher, Michael; Adami, Valentina; Bellosta, Paola; et al.
Abstract: Intronic GGGGCC (G4C2) hexanucleotide repeat expansion within the human C9orf72 gene represents the most common cause of familial forms of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) (C9ALS/FTD). Repeat‐associated non‐AUG (RAN) translation of repeat‐containing C9orf72 RNA results in the production of neurotoxic dipeptide‐repeat proteins (DPRs). Here, we developed a high‐throughput drug screen for the identification of positive and negative modulators of DPR levels. We found that HSP90 inhibitor geldanamycin and aldosterone antagonist spironolactone reduced DPR levels by promoting protein degradation via the proteasome and autophagy pathways respectively. Surprisingly, cAMP‐elevating compounds boosting protein kinase A (PKA) activity increased DPR levels. Inhibition of PKA activity, by both pharmacological and genetic approaches, reduced DPR levels in cells and rescued pathological phenotypes in a Drosophila model of C9ALS/FTD. Moreover, knockdown of PKA‐catalytic subunits correlated with reduced translation efficiency of DPRs, while the PKA inhibitor H89 reduced endogenous DPR levels in C9ALS/FTD patient‐derived iPSC motor neurons. Together, our results suggest new and druggable pathways modulating DPR levels in C9ALS/FTD. Synopsis: GGGGCC repeat expansion in the C9orf72 gene causes amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) in part via neurotoxic dipeptide‐repeat proteins (DPRs) produced by repeat‐associated non‐AUG translation. Here, a high‐throughput drug screen identifies novel positive and negative small‐molecule modulators of DPR levels. cAMP‐elevating compounds increase DPR levels by enhancing protein kinase A (PKA) activity. PKA inhibition reduces DPR levels in cells and in C9ALS/FTD patient‐derived iPSC motor neurons. Inhibition or knockdown of PKA ameliorates motility and survival in a Drosophila model of C9orf72 ALS/FTD. Knockdown of PKA catalytic subunits correlates with reduced DPR translation efficiency. HSP90 inhibitor geldanamycin and aldosterone antagonist spironolactone reduce DPR levels by promoting protein degradation. Abstract : Screening small‐molecule agonists for the ability to modulate accumulation of toxic polypeptides suggests PKA signaling, proteasomal and autophagy pathways as potential therapeutic targets for C9orf72‐associated ALS/FTD.